THE INFLUENCE OF ORGANIZATIONAL CULTURE AND COMPENSATION ON EMPLOYEE PERFORMANCE WITH MOTIVATION AS AN INTERVENING VARIABLE AT JALA AMMARI HOSPITAL MAKASSAR CITY - Marhawati Marhawati; Cepi Pahlevi; Muhammad Sobarsyah (Hasanuddin Journal of Applied Business and Entrepreneurship, 2022)
This study aims to determine the effect of organizational culture and compensation on employee performance with motivation as an intervening variable at Jala Ammari Hospital Makassar. The number of samples in this study was 43 people, the type of research used was quantitative research with survey research. The results of this study show that organizational culture and compensation variables have a positive and significant effect on employee motivation at Jala Ammari Hospital Makassar City, then employee motivation variables have a positive and significant impact on employee performance at Jala Ammari Hospital Makassar City, organizational culture variables do not have a positive effect on employee performance at Jala Ammari Hospital Makassar City, the compensation variable has no positive effect on employee performance at Jala Ammari Hospital Makassar City, organizational culture variable has a positive and significant effect on employee performance with overall motivation. as the intervening variable at Jala Ammari Hospital Makassar City, and the compensation variable has a positive and significant effect on employee performance with motivation as an intervening variable at Jala Ammari Hospital Makassar City